Optimal use of intranasal corticosteroids and intranasal saline, is there a clear answer?. Issue 4 (August 2021) - Freeman, Catherine M.; Rank, Matthew A.
Abstract : Purpose of review: Chronic rhinosinusitis (CRS) is a prevalent condition that poses a significant burden on both quality of life and healthcare utilization. Notwithstanding the heterogenous nature of CRS endotypes and phenotypes, isotonic saline and corticosteroids are recommended as first line medical therapy by recent clinical guidelines. We provide an overview of recent studies of topical saline and corticosteroids for people with CRS and emphasize areas of unmet needs. Recent findings: Recent trials suggest exhalation delivery systems of corticosteroid are effective and well tolerated but did not involve comparison with another active treatment. Recent comparative efficacy studies show no clear differences in doses of topical corticosteroid, method of topical corticosteroid delivery, advantage over macrolide antibiotic, or method or type of saline irrigation. Summary: The preeminent formulation, dosage, and delivery of topical corticosteroid and saline for people with CRS represents an area of ongoing research need.